Conditio humana: Az Aranysárkány biopoétikai megközelítése - Dobos, István (Studia Litteraria, 2018)
So far, this piece by Dezső Kosztolányi has not been analyzed from the aspect of biopoetics. The novel seeks to answer the query whether we are able to transcend the framework of interpreting ourselves that is traditionally available for us and move to the level of other relationships of existence (present in the vegetable or animal kingdoms, or in nature) in this effort. In Aranysárkány [verbatim: golden dragon], the eponymous creature is neither a human being, nor an animal, but a model of a mythological beast, which the characters seem to personify in various ways. Its role in the book is to gradually undermine the anthropological conviction that considers human beings to be the opposite of animals. according to this latter assumption, our absolute superiority in this respect is guaranteed by our intellect, willpower, morality, and the use of language. The novel suggests that the differences and discrepancies that separate us from animals and other natural creatures are much more complex and the essence of human existence cannot be defined or pinpointed through simple binary oppositions. it is the act of being addressed by the imaginary gaze of the golden dragon and the effort of embedding the interpretation of the experience of this encounter into the image perceptible about human nature that provide the perspectives and angles of comprehension which may justify the possibility of approaching Kosztolányi’s Aranysárkány from a bio-poetic aspect.